2014
DOI: 10.1038/nsmb.2795
|View full text |Cite
|
Sign up to set email alerts
|

Human immunoglobulin E flexes between acutely bent and extended conformations

Abstract: Crystallographic and solution studies have shown that IgE molecules are acutely bent in their Fc region. Crystal structures reveal the Cε2 domain pair folded back onto the Cε3-Cε4 domains, but is the molecule exclusively bent or can the Cε2 domains adopt extended conformations and even “flip” from one side of the molecule to the other? We report the crystal structure of IgE-Fc captured in a fully extended, symmetrical conformation and show by molecular dynamics, calorimetry, stopped-flow kinetic, SPR and FRET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(107 citation statements)
references
References 69 publications
8
98
1
Order By: Relevance
“…Structural studies of secreted IgE indicated that an asymmetric bend can occur in IgE at the CH2-CH3 linker region, causing one of the two CH2 domains to fold back onto the CH3 and CH4 domains, making particularly extensive contacts with the CH3 domain (Wan et al, 2002). Recent evidence suggests that this bent shape can also be extended, which can subsequently allow CH2 to flip from one side of CH3-CH4 to the other (Drinkwater et al, 2014). It seems plausible that for the membrane IgE BCR, the ability to adopt an asymmetric bend conformation mimics antigen binding.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of secreted IgE indicated that an asymmetric bend can occur in IgE at the CH2-CH3 linker region, causing one of the two CH2 domains to fold back onto the CH3 and CH4 domains, making particularly extensive contacts with the CH3 domain (Wan et al, 2002). Recent evidence suggests that this bent shape can also be extended, which can subsequently allow CH2 to flip from one side of CH3-CH4 to the other (Drinkwater et al, 2014). It seems plausible that for the membrane IgE BCR, the ability to adopt an asymmetric bend conformation mimics antigen binding.…”
Section: Discussionmentioning
confidence: 99%
“…IgY is evolutionarily most closely related to IgG and IgE (2). Similar to IgY, IgE does not have a hinge, and recent studies indicate that the Fc portion of this molecule folds back upon itself (31), which may explain the unusual appearance of the Fc in 7S IgY. Other Igs also have flexible Fc.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly the complementarity-determining region, CDR3 H3 loop, of the Fab fragment penetrated deep into the GPCR, mimicking the CDR3 of the VHH in the Rasmussen paper [25], and showing that extended CDR loops are not the sole preserve of nanobodies. While GPCRs have been the focus of much of the pioneering work with antibody fragment-definition of conformations, a new perspective on IgE function in allergen recognition has been achieved through study of a diversity of conformational states [29]. A function-modifying antibody Fab fragment was shown to hold the Cε2 and Cε3 domains in a linear structure which precluded receptor binding, validating molecular dynamics predictions of IgE Fc conformational sampling.…”
Section: Definition Of Functionally Relevant Conformations Of Proteinsmentioning
confidence: 98%